An Analysis of Teachers’ Strategies in Using Media to Teach English at EFL Class - Nur Husnil Khatimah; Sukmawati Yasim; Indiana Indiana (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2023)
The objectives of this study were to investigated (1) media that used   by the English teachers in teaching English at SMPN 3 Tinambung, (2) strategies that teachers used the media in teaching English. This study used qualitative research method. The subjects of this study were two English teachers at SMPN 3 Tinambung. The data were collected through observation and interview. The observation was done by using field notes observation and interview was done by using interview guideline. The results of this study showed that teachers were used media in the teaching learning process. Teachers were used visual media such as English book, whiteboard, worksheet, key answer test and multimedia such as mobile phone. The teachers’ strategies in selected the media were selected and determined the media that was used to teach English, based on the RPP and pay attention to the purpose of the study, the effectiveness of the media, materials have been thaught, the availability of the media, and also students’ characteristics. Teachers’ strategies to used those media were the teachers prepared the media before using them, pay attention of the activities in using the media and follow-up activities after using the media. The way the teachers used the media to teach English were the teachers explained the materials by using English book and by writing materials, vocabulary or to draw picture with using whiteboard. Teachers also used key answer test when they work the tasks together with students and then if the teachers looking for additional materials on the internet, teacher was used mobile phone to access the internet. As  an suplementary tasks, the teachers gave the students worksheet to do after teaching learning process.